Influence of Closed-loop Target-controlled Infusion of Propofol on Anesthesia Depth during Elderly Hip Replacement - Chen Qian; Li Chabing; Jiang Tao; Kang Lu; Wang Yiqiao (Guoji laonian yixue zazhi)
Objective To explore the influence of closed-loop target-controlled infusion of propofol during elderly hip replacement on anesthesia depth. Methods The data of 80 elderly patients with hip replacement in Anhui No.2 Provincial People Hospital were retrospectively analyzed from January 2021 to March 2024. According to the bispectral index (BIS) interval during propofol closed-loop target-controlled infusion, they were divided into group D (BIS of 40-49, 43 cases) and group L (BIS of 50-59, 37 cases).The surgical conditions, intraoperative hemodynamics, dosage of propofol, utilization rate of vasoactive drugs, recovery status, cognitive function and incidence rate of delirium were compared between groups. Results There was no significant difference between the two groups in surgical time,intraoperative bleeding and intraoperative hemodynamics(P>0.05). In group D, thedosage of propofol was greater than that in group L(P<0.05), and the utilization rate of vasoactive drugs was higher than that in group L(P<0.05); the extubation time in group D was longer than that in group L(P<0.05), and there was no significant difference in the duration of anesthesia care unit stay between the two groups (P>0.05); the simple cognitive assessment scale score in group D was lower than that in group L at 3 days after surgery (P<0.05), and the incidence of delirium within 3 days after surgery was higher than that in group L(P<0.05). Conclusion Closed-loop target-controlled infusion of propofol under relatively light anesthesia maintenance during hip replacement in elderly patients is helpful for early postoperative recovery, and can avoid cognitive impairment and reduce the risk of delirium.